Viruses and Bacteria – Antiviral and Antibacterial Textile Materials: A Review - Kimiasadat Hosseini Kalahroodi; Sheila Shahidi; Bahareh Moazzenchi; Rattanaphol Mongkholrattanasit (Tekstilec, 2024)
Protective textiles, such as antiviral and antimicrobial textiles, are essential for daily human health during pandemics. This paper focused on different studies of bacteria, the classification of viruses and features, different antibacterial and antiviral agents, and the manufacture of antibacterial and antiviral textiles and masks. This review primarily considered the representative specifications of ideal antiviral agents compatible with antimicrobial textile purposes.